Optimization of gum combination for instant pudding based on creep and recovery parameters by mixture design approach - Dogan, Mahmut; Ersoz, Nevruz Berna; Toker, Omer Said; Kaya, Yahya; Caniyilmaz, Erdal (SPRINGER, 2014)
In the present study, gum combinations used in the pudding formulation were optimized by mixture design approach based on creep and recovery measurements. For this aim, four different gums (carrageenan, alginate, guar and xanthan gum) and their different combinations were used in the formulation. The creep-recovery properties of the pudding samples prepared with different gums or gum combinations were investigated. Burger model was satisfactorily applied for the determination of the creep-recovery characteristics of the samples. The use of the carrageenan in the pudding formulation caused a decrease in deformation of the samples. Gel strength value of the pudding samples was also calculated using the data. In order to optimize the gum combination based on the creep-recovery measurements, mixture design was carried out, and it was seen that established models satisfactorily predicted the viscoelastic parameters of the samples. During the optimization of the gum combination used in the pudding formulation, desirability function was used to optimize the ingredients simultaneously based on the requirements. The gum combination including 59.5 % carrageenan and 40.5 % guar gum or 52.7 % carrageenan, 33.8 % guar gum and 13.5 % xanthan gum was determined to be the optimum in terms of quality of the product.
Keywords: Pudding; Gum; Creep-recovery properties; Gel strength; Mixture design; RHEOLOGICAL PROPERTIES; SENSORY PROPERTIES; ALGINATE GELS; SHEAR CREEP; GUAR GUM; BEHAVIOR; TEMPERATURE; BEEF; Food Science & Technology